Fetal Doppler velocimetry and bronchopulmonary dysplasia risk among growth-restricted preterm infants: an observational study. Issue 7 (20th July 2017) - Lio, Alessandra; Rosati, Paolo; Pastorino, Roberta; Cota, Francesco; Tana, Milena; Tirone, Chiara; Aurilia, Claudia; Ricci, Cinzia; Gambacorta, Alessandro; Paladini, Angela; Mappa, Ilenia; Buongiorno, Silvia; et al.
Abstract : Objective: To investigate whether fetal growth restriction (FGR) diagnosis, based on pathological prenatal fetal Doppler velocimetry, is associated with bronchopulmonary dysplasia (BPD) independently of being small for gestational age (SGA) per se at birth among very preterm infants. Design: Prospective, observational study. FGR was defined as failing fetal growth in utero and fetal Doppler velocimetry abnormalities. Setting: Policlinico Universitario Agostino Gemelli, Roma, Italy. Patients: Preterm newborns with gestational age ≤30 weeks and birth weight (BW) ≤1250 g. Main outcome measures: Bronchopulmonary dysplasia. Results: In the study period, 178 newborns were eligible for the study. Thirty-nine infants (22%) were considered fetal growth-restricted infants. Among the 154 survived babies at 36 weeks postmenstrual age, 12 out of 36 (33%) of the FGR group developed BPD versus 8 out of 118 (7%) of the NO-FGR group (p<0.001). BPD rate was sixfold higher among the SGA-FGR infants compared with the SGA-NO-FGR infants. In a multivariable model, FGR was significantly associated with BPD risk (OR 5.1, CI 1.4 to 18.8, p=0.01), independently from BW z-score that still remains a strong risk factor (OR 0.5, CI 0.3 to 0.9, p=0.01). Conclusion: Among SGA preterm infants, BPD risk dramatically increases when placenta dysfunction is the surrounding cause of low BW. Antenatal fetal Doppler surveillance could be a useful tool for studying placenta wellness and predicting BPD risk among preterm babies. Further research is needed to better understand how FGR affects lung development.